Strength and Deformation Behaviour of Cemented Paste Backfill in Sub-zero Environment - Chang, Shuang (Université d'Ottawa / University of Ottawa, 2016)
Underground mining produces a huge amount of voids and an even larger quantity of mine waste. Overlooking these voids could lead to the possibility of ground subsidence, as well as safety issues during mining operation; while ignoring the waste, could cause environmental pollution and significant suffering. One solution to remedy both (the voids and the waste) is cemented paste backfill (CPB), which is gaining increased recognition in both the mining industry and academic research. Transforming tailings into cemented paste, and transporting this back to underground stopes, not only negates these safety issues to a large degree, but also makes it possible to put waste to good use.However, most studies involving CPB have been conducted at temperatures above 0°C; knowledge of CPB in sub-zero environments is still lacking. For this reason, this thesis investigates the mechanical behaviour of CPB in a the latter type of environment.Uniaxial compressive strength tests were carried out on a series of frozen CPB (FCPB) samples to evaluate the mechanical behaviour (e.g. compressive strengths, geotechnical features, and the stress-strain relationships) of FCPB. It has been discovered in this thesis that FCPB exhibits remarkable strength compared to CPB and, has a great resemblance to frozen soil. Factors which may affect the behaviour of FCPB were thoroughly examined. Binder contents and types were found to be irrelevant; water content, in contrast, plays a dominant role, with an optimum value of around 26% by weight. Sulphate was confirmed to have an adverse effect on the strength of FCPB due to the increasing unfrozen water content and the formation of legible ice lenses. Hydraulic conductivity tests, scanning electron microscope observations, thermal gravimetric analyses, and mercury intrusion porosimetry were also performed as subsidiary experiments to understand the geotechnical features of FCPB. This information will be of significant value for numerous practical applications.
Keywords: Cemented paste backfill; Sub-zero temperature; Tailings; Strength